VALUE OF FRACTAL ANALYSIS OF OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN VARIOUS STAGES OF DIABETIC RETINOPATHY. Issue 9 (September 2018) - Bhardwaj, Suruchi; Tsui, Edmund; Zahid, Sarwar; Young, Emma; Mehta, Nitish; Agemy, Steven; Garcia, Patricia; Rosen, Richard B.; Young, Joshua A.
Abstract : Purpose: To use fractal dimensional analysis to investigate retinal vascular disease patterns in patients with diabetic retinopathy using spectral domain optical coherence tomography angiography. Methods: A retrospective study was conducted which included 49 eyes from 26 control subjects and 58 eyes from 35 patients known to have diabetic retinopathy. Of the 58 eyes with known retinopathy, 31 were categorized as nonproliferative diabetic retinopathy (13 mild, 9 moderate, and 9 severe) and 27 were categorized as proliferative diabetic retinopathy. Optical coherence tomography angiography images were acquired using the RTVue XR Avanti (Optovue, Inc). Automated segmentation was obtained through both the superficial and deep capillary plexuses for each eye. Grayscale optical coherence tomography angiography images were standardized and binarized using ImageJ (National Institutes of Health). Fractal box-counting analyses were conducted using Fractalyse (ThéMA). Fractal dimensions (FDs) and correlation coefficient of the superficial and deep capillary plexuses were compared between control eyes and those in various stages of diabetic retinopathy. Results: The superficial and deep capillary plexuses from diabetic and control eyes were analyzed. The average FD for diabetic eyes was significantly lower than in control eyes in the superficial plexus ( P = 2.4 × 10 −6 ) and in the deep capillary plexus ( P = 1.87 × 10 −12 ) with a more statistically significant difference noted in the deep capillary plexus. When analyzing diabetic patients without edema noted on optical coherence tomography, the FD was significantly reduced in the superficial ( P = 0.001) and deep ( P = 1.49 × 10 −6 ) plexuses. When analyzing diabetic patients with edema noted on optical coherence tomography, the FD was significantly reduced in the superficial ( P = 2.0 × 10 −5 ) and deep ( P = 1.85 × 10 −9 ) plexuses. Conclusion: The optical coherence tomography angiography FD is significantly lower in both superficial and deep capillary plexuses in eyes with all stages studied of diabetic retinopathy. The results were more often significant for the deep capillary plexus. The use of fractal analysis provides an objective criterion to assess microvascular disease burden in diabetic retinopathy. Abstract : This study uses fractal dimension analysis to study optical coherence tomography angiography images of patients with various stages of diabetic retinopathy. The results are compared with control patients to understand how fractal dimension changes as the stage of diabetic retinopathy changes.